Size Engineering of Ti3C2Tx Nanosheets for Enhanced Supercapacitance Performance - Haosheng Liu; Xin Chang; Lu Li; Mingyi Zhang (Molecules)
In this research, we synthesized a series of Ti3C2Tx nanosheets with varying lateral dimensions and conducted a thorough investigation into the profound relationship between the electrochemical performance of Ti3C2Tx materials and their lateral sizes. This study innovatively incorporates a clever combination of small-sized and large-sized Ti3C2Tx nanosheets in the electrode preparation process. This strategy yields excellent results at low scan rates, with the fabricated electrode achieving a high volumetric capacitance of approximately 658 F/g. Even more remarkable is the fact that, even under extreme testing conditions where the scan rate surges to 10 V s−1, the electrode retains its capacitive characteristics robustly without any significant performance degradation. These outstanding characteristics underscore the exceptional ability of Ti3C2Tx electrode materials to maintain high energy storage capacity during rapid charge–discharge cycles, holding significant importance for advancing the development of electrochemical energy storage devices with fast response times and high power densities.